The Development of STEM-based Physics e-Workbook with Project-based Learning Activities - Nida, Ria Rahma; Siregar, Eveline; Chaeruman, Uwes Anis (FKIP Universitas Lampung, 2023)
Abstract: The Development of STEM-based Physics e-Workbook with Project-based Learning Activities. Objective: There are various media that are effective in helping students understand learning material at school but teachers have not used them optimally. This study aims to develop digital workbooks with a feasible and effective project-based learning approach in physics subjects. Methods: This development uses the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The product feasibility test was carried out through the assessment of media experts, material experts, and was tested on class VII students at SMPN 1 Bandar Lampung. Findings: The results of the effectiveness test were obtained through the pretest and posttest. The results of the due diligence by material experts and media experts obtained a proportion of reporting rates of 85.71% and 95.45% so that digital workbooks fall into the category of appropriate use. The one-to-one trial shows that digital workbooks are in the very good category with an average proportion of sales rate of 91.66%. In addition, the small group trial also showed an average proportion of the reporting rate of 89.74%, so it was included in the very good category. The results of the effectiveness test by calculating the n-gain score obtained a result of 60.8 so that the digital workbook can be said to be quite effective. Conclusion: Based on these results, it can be interpreted that STEM-based digital Physics workbooks with a project-based learning approach for junior high school students are appropriate and effective for use. Keywords: ADDIE, digital workbook, project-based learning, STEM DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp944-957